(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2019)
The rapid growth of information and communication technology has made it possible for everybody to search information and be more efficient in their work. Another shift taking place as a result of the advancement of surveillance technologies involves the control of personal data. Controlling personal data enables employers to monitor work performance as well as maintaining employee discipline and productivity. The new technology involved includes global positioning systems, video surveillance, smart cards, face recognition and biometrics. The collection of personal data has significant importance with regard to privacy. The Malaysian Federal Constitution does not specifically recognize privacy as a fundamental right, while the Personal Data Protection Act 2010 only protects the handling of personal data in commercial transactions. As such, this article discusses the extent to which protection is available to employees relating to privacy. The doctrinal methodology was employed in conducting this research. Cases from the European Union and the United States of America were used as guides and for comparison with the situation in Malaysia. The findings are that there is no protection of privacy at the workplace provided specifically to protect employees in Malaysia. Keywords: privacy, workplace privacy, personal data, surveillance, employee rights